Effectiveness of DIR/Floortime Intervention on Communication Skills Development in Elementary School Students with Autism Spectrum Disorder - Dwidjantoro, Muhammad Irma Sunu; Sukinah, Sukinah (Journal of Innovation and Research in Primary Education, 2025)
Communication impairments represent core challenges in children with Autism Spectrum Disorder (ASD), significantly impacting academic and social functioning. The Developmental, Individual-differences, Relationship-based (DIR)/Floortime intervention shows promise for addressing these deficits, yet limited research has examined its effectiveness in elementary school settings. This study employed a single-subject research design with A-B-A' reversal methodology to examine DIR/Floortime intervention effects on communication skills in a 10-year-old male student with ASD. The participant was enrolled in fourth grade at an elementary school in Telen District. Data collection utilized direct behavioral observation and performance-based assessment across three phases: baseline 1 (4 sessions), intervention (6 sessions), and baseline 2 (4 sessions). The DIR/Floortime protocol followed established five-phase procedures including observation, opening communication circles, following the child's lead, expanding interactions, and natural closure. Data analysis employed within-condition and between-condition analyses, including trend analysis, stability assessment, and data overlap calculations. Systematic improvements were observed across intervention phases. Mean scores increased from 29.72 in baseline 1 to 77.1 during intervention, with maintenance at 93.8 in baseline 2, representing a 215% improvement from initial baseline. Between-condition analysis revealed 0% data overlap across phase transitions, indicating exceptionally strong intervention effects. Within-condition analysis showed 100% stability in baseline 2, confirming sustained skill acquisition. The findings provide robust evidence for DIR/Floortime effectiveness in elementary school settings. Results extend previous research by demonstrating successful implementation in educational environments, supporting cost-effective, relationship-based interventions that promote lasting communication improvements. The 0% data overlap establishes clear functional relationships between DIR/Floortime and communication skill development, aligning with systematic reviews supporting DIR/Floortime as an evidence-based practice for children with ASD.